Multistatic Wireless Fidelity Network Based Radar – Results of the Chrcynno Experiment - Rzewuski, Stanislaw; Wielgo, Maciej; Klincewicz, Karol; Podkalicki, Lukasz; Kulpa, Krzysztof; Malanowski, Mateusz (Společnost pro radioelektronické inženýrství, 2014)
This paper presents the theory and experimental result of passive radar using WIFI transmitters as illuminators of opportunity. As a result of experiments conducted on 17th August 2013 at airfield Chrcynno a Cessna C208 airplane was detected and tracked using multistatic passive radar system based on low power signal from WIFI network nodes, which were acting as non cooperative illuminators of opportunity. In the experiment 3 wireless access points were communicating with each other and illuminating the radar scene (airfield). The direct reference and reflected (surveillance) signals have been acquired and processed using specially developed algorithm presented in the paper. After signal processing using Passive Coherent Location methods target has been detected. This paper describes in details the algorithms and the results of the experiment for the multistatic passive radar based on the WIFI signal.
Keywords: Passive radar systems; passive coherent location; passive bistatic radar; multistatic passive radio location; noise radars; WIFI signal decoding; frame detection; processing signal from wireless networks